A Critical Review of Deployable Truss Masts and Proposal of a New Mast: Hidam - Demirel, Murat; Cebeci, Y.; Kiper, Gökhan; Demirel, M.; Kiper, G. (Springer Nature, 2023)
This paper investigates the factors which affect the packing ratio of deployable articulated truss masts and investigates the necessary design criteria for new designs with enhanced packing ratio. First, the available deployable articulated truss masts are examined, and the design parameters of these structures are worked out. Then a novel design called HiDAM is proposed with superior packing ratio compared to similar ones in the literature. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Deployable Mast; Deployable Structures; Satellite Components